PENGARUH COSTUMER EXPERIENCE, STORE ATMOSPHERE DAN PERSONALITY COSTUMER TERHADAP REVISIT INTENTION KONSUMEN PADA NOKA COFFE SUNGAI PENUH - Satria, Edia; Baviga, Rio; Cayanti, Karin Septi (Gapenas Publisher, 2025)
This study aims to determine the effect of Costumer Experience, Store Atmosphere and Personality Costumer on Revisit Intention partially and simultaneously. The object of this study is Noka Coffee Sungai Penuh, respondents in this study are consumers who have visited more than 2 times. The number of respondents in this study is 80 respondents. Based on the results of the previous analysis and discussion, it can be concluded as follows: Costumer Experience has a significant effect on Revisit Intention of Noka Coffee Consumers, this is evidenced by t count> t table (2.132> 1.99167), Store Atmosphere has a significant effect on Revisit Intention at Noka Coffee Sungai Penuh, this is evidenced by t count> t table (2.934> 1.99167), Personality Costumer has a significant effect on Revisit Intention of Noka Coffee Sungai Penuh Consumers and this is evidenced by t count> t table (6.161> 1.99167).